Surgical treatment of breast cancer - Bedoya Hevia, Mariano (2015)
Our behavior we adopt the criterion of "operability" of Haagansen and Stout and continue practicing Radical Mastectomy associating postoperative radiotherapy, and for the moment we do not support expanded operations: a) the supraclavicular for consideration at the group of inoperable b) of the internal mammary chain, because we expect to be sanctioned by time; rather we advise exploratory behavior, in order to establish an accurate forecast. We recommended in elderly with high surgical risk and simple mastectomy and ulcerated tumors as a palliative measure. We remove the only recurrences and ordered the radiotherapy treatment. The oophorectomy in young, we do not do routine; remissions observed when practiced in recurrences and metastases. The other procedures await the sanction of time.